2013
DOI: 10.2174/1874306401307010083
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Pulmonary Function Measured in Children Exposed to High Environmental Relative Moldiness Index Homes

Abstract: Background:Exposures to water-damaged homes/buildings has been linked to deficits in respiratory health. However, accurately quantifying this linkage has been difficult because of the methods used to assess water damage and respiratory health.Purpose:The goal of this analysis was to determine the correlation between the water-damage, as defined by the Environmental Relative Moldiness Index (ERMI) value in an asthmatic child’s home, and the child’s pulmonary function measured by spirometry, “forced expiratory v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Indeed, molds can produce mycotoxins, spores, hyphae, and wall fragments containing (1 → 3)-β-D-glucans and proteins which could induce allergic reactions of types I, III, and IV (Douwes et al 2003 ; Seo et al 2008 ). Some studies revealed an association between the fungal levels in the air and the occurrence of allergy (Horner et al 1995 ; Meheust et al 2014 ; Mendell et al 2011 ; Reboux et al 2010 ) and between water-damaged buildings and human exposure to fungal contamination present in indoor air (Jones et al 2011 ; Vesper et al 2013 ). Presently, with the climate change, the new energy conservation measures, the development of the urbanization, and the considerable amount of time spent inside buildings, people are increasingly exposed and might be more susceptible to developing a respiratory problem caused by a fungal contamination (de Ana et al 2006 ; Mendell et al 2011 ; Sharpe et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, molds can produce mycotoxins, spores, hyphae, and wall fragments containing (1 → 3)-β-D-glucans and proteins which could induce allergic reactions of types I, III, and IV (Douwes et al 2003 ; Seo et al 2008 ). Some studies revealed an association between the fungal levels in the air and the occurrence of allergy (Horner et al 1995 ; Meheust et al 2014 ; Mendell et al 2011 ; Reboux et al 2010 ) and between water-damaged buildings and human exposure to fungal contamination present in indoor air (Jones et al 2011 ; Vesper et al 2013 ). Presently, with the climate change, the new energy conservation measures, the development of the urbanization, and the considerable amount of time spent inside buildings, people are increasingly exposed and might be more susceptible to developing a respiratory problem caused by a fungal contamination (de Ana et al 2006 ; Mendell et al 2011 ; Sharpe et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, an increasing amount of studies are focused on fungal indoor contamination and its impact on public health [9, 10, 15, 2832]. To rapidly detect and identify the fungal contaminants, qPCR holds a great potential in comparison to the classical methods based on plate counting and microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, one recent study found higher ERMI values in school dust from schools with high prevalence of asthma as compared to schools with low asthma prevalence . Finally, one study found lower lung function (FEV1) among children who lived in homes with higher ERMI values .…”
mentioning
confidence: 98%